International Human Rights Law: Protection of Refugees in Contemporary Conflicts - Deo Renaldi Saputra; Sahal Hanafi; Sunusi Dauda; Melva Noya; Bunga Dwi Fani Ritonga (International Journal of Law and Political Authority, 2026)
Contemporary armed conflicts have generated complex patterns of forced displacement that challenge the adequacy of traditional refugee protection frameworks. This article examines the role of international human rights law in safeguarding refugees within the context of modern conflicts characterized by protracted violence, institutional fragility, and evolving displacement drivers. Using a normative legal research methodology, the study analyzes the convergence between international human rights law, refugee law, and international humanitarian law, with particular attention to enforcement mechanisms and judicial practice. The findings reveal that human rights law provides a universal and enforceable normative foundation that extends protection beyond formal refugee status, strengthens the principle of non-refoulement, and enhances accountability through judicial oversight. The article further identifies emerging challenges, including temporary protection regimes, climate-related displacement, and digital governance, which require adaptive human rights-based responses. By situating refugee protection within a rights-centered legal framework, this study underscores the continuing relevance of international human rights law as a vital instrument for protecting displaced populations amid increasingly complex and unstable global conflict environments.